2013
DOI: 10.1097/nnr.0b013e3182a0316b
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Health Choices for Young Adults With Sickle Cell Disease or Trait

Abstract: Background People with sickle cell disease (SCD) or sickle cell trait (SCT) may not have information about genetic inheritance needed for making informed reproductive health decisions. CHOICES is a web-based, multimedia educational intervention that provides information about reproductive options and consequences to help those with SCD or SCT identify and implement an informed parenting plan. Efficacy of CHOICES compared with usual care must be evaluated. Objective The purpose was to compare immediate postte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 37 publications
1
43
0
Order By: Relevance
“…The criteria for selection of the participants for the RCT are reported elsewhere (Wilkie et al . ).…”
Section: The Studymentioning
confidence: 97%
See 1 more Smart Citation
“…The criteria for selection of the participants for the RCT are reported elsewhere (Wilkie et al . ).…”
Section: The Studymentioning
confidence: 97%
“…We then conducted a 2‐year randomized controlled trial (RCT) where the immediate post‐test effects of the CHOICES program demonstrated increased reproductive health knowledge and intentions to implement a parenting plan prior to pregnancy compared with the e‐Book or usual care program (Wilkie et al . ). Although these findings were encouraging, insights about the participants’ views about parenthood and study participation would strengthen educational efforts and guide development of a national representative intervention study.…”
Section: Introductionmentioning
confidence: 97%
“…Whereas other studies have examined important topics like reproductive decision making and genetic inheritance knowledge of individuals with SCD or SCT, few if any addressed sexual health and genetic knowledge and needs of youth with SCD. 36,37 …”
Section: Dicussionmentioning
confidence: 99%
“…This is consistent in our study in that a minority of participants thought that it is possible to have a child with SCD prior to pregnancy even in those who knew their SCT status. Educational interventions, similar to the web‐based CHOICES, could be beneficial in providing education and altering intentions, though longer follow‐up may be necessary to see an advantage 3,31 . Further research is needed to understand the optimal interventions.…”
Section: Discussionmentioning
confidence: 99%